Assessment of Nurse’s Knowledge and Practices about Personal Protective Equipment in Hemodialysis Unit in Basra Teaching Hospital - Ahmed T. Saud; Aliaa H. Ali (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: to assess the nurses’ knowledge and practices about personal protective equipment (PPE).Methodology: A descriptive cross-sectional design study has been carried out in Basrah teaching hospital,A purposive (non-probability) sample consist of (34) nurses who worked in the units of hemodialysis, thestudy started from 18th of October, 2019 to 12th of July, 2020. The instrument of the present study containsthree parts, first part: It is concerned with the nurse’s demographic data, second part: it is composed of (10)multiple choice questions (MCQs) related to the nurses knowledge, and third part: it consists of (14) itemsfor nurses practice about personal protective equipment. The validity of the instrument had been achieved by8 experts from different scientific branches. Statistical programs such as SPSS (Statistical Package for SocialScience) v. 23 were used to analyze the data. Result: the findings revealed that majority of nurses had poorknowledge and practice about personal protective equipment and there has been a significant relationshipbetween the nurse’s knowledge about personal protective equipment and their level of education at a p<0.05level. Recommendation: Provide training programs for the hemodialysis nurses on the promotion of higherstandards of the hand hygiene and potential uses of the personal protective equipment during working inhemodialysis centers.